Effects of Phytobiotic of Curcuma aeruginosa, Curcuma longa and Zingiber officinale on the Performance and Carsass Quality in Broiler: Pengaruh Fitobiotik Temu Ireng (Curcuma aeruginosa), Kunyir (Curcuma longa) Dan Jahe Merah (Zingiber officinale) Terhadap Performa Dan Kualitas Karkas Ayam Pedaging - Maksudi Maksudi; Fahmida Manin; Sri Wigati; A Insulistyawati (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2018)
The purpose of this study was to investigate the effects of the use natural antibiotics (phytobiotic) Curcuma aeruginosa, Curcuma longa and Zingiber officinale as an alternative antibiotic on the performance of broiler. Experimental design was a Completely Randomized Design using 440 broiler of one day-old chicks and randomly divided into 11 treatments with 4 chickens for each treatmen. The dietry treatments were negative control (T01), a basal diet without any feed additives and positive control (T02), a basal diet with bacitracin, and basal diets with additional different levels (0.75, 1.0, and 1,5%) of Curcuma aeruginosa (TI1, TI2, and TI3), Curcuma longa (KU1, KU2, and KU3) and red ginger (JM1, JM2, and JM3), respectivelly. The results showed that the addition of low-dose phytobiotic (0.75%) in broiler have produced a different effect (P <.05) on the parameters of performance, but at higher doses, the results tend to show the opposite effect. However, low-dose treatment phytobiotic parameters showed no differences (P>.05) with positive control treatment of bacitracin. In conclusion, the use of phyitobiotics Curcuma aeruginosa, Curcuma longa and red ginger has showed their function as growth promoters in low dose.